Association between exercise habits in adolescence and old age and the risk of mild cognitive impairment: the Bunkyo health study - Shi, Huicong; Tabata, Hiroki; Otsuka, Hikaru; Iwashimizu, Takahito; Kaga, Hideyoshi; Someya, Yuki; Abudurezake, Abulaiti; Kakehi, Saori; Naito, Hitoshi; Yoshizawa, Yasuyo; Kawamori, Ryuzo; Watada, Hirotaka; et al. (Frontiers in Aging Neuroscience, 2024)
BackgroundExercise in adolescence and old age improves cognitive function in older adults, but the combined effect of exercise habits in both periods is controversial. This study aimed to clarify the relationship between exercise habits in adolescence and old age and mild cognitive impairment (MCI) and to compare regional brain volumes and blood biochemical markers associated with cognitive function in older adults.MethodsBaseline data of 1615 participants aged 65–84 years from the Bunkyo Health Study were analyzed. MCI was diagnosed using the Japanese version of the Montreal Cognitive Assessment. Participants were divided into four groups based on their exercise habits in adolescence (13–18 years) and old age: no exercise in either period (None-None), exercise in adolescence only (Active-None), exercise in old age only (None-Active), and exercise in both periods (Active-Active). Logistic regression models estimated the odds ratios (ORs) of MCI prevalence. Regional brain volumes, such as the prefrontal cortex, temporal lobe, parietal cortex, and hippocampus, and blood biochemical markers, such as BDNF, IGF-1, and homocysteine, were compared between groups.ResultsThe OR for MCI was significantly lower in the Active-Active group than in the None-None group (OR, 0.62; 95% CI, 0.41–0.94). However, there were no significant differences in regional brain volumes and blood biochemical markers between the Active-Active and None-None groups.ConclusionsOlder adults with exercise habits in both adolescence and old age have a lower risk of MCI. However, specific regional brain volumes and biochemical markers may not be associated with differences in cognitive function in older adults.